Correlating Nitrile IR frequencies to local electrostatics quantifies noncovalent interactions of peptides and proteins - Deb, Pranab; Haldar, Tapas; Kashid, Somnath M.; Banerjee, Subhrashis; Chakrabarty, Suman; Bagchi, Sayan (Journal of Physical Chemistry B, 2016)
Noncovalent interactions, in particular the hydrogen bonds and nonspecific long-range electrostatic interactions are fundamental to biomolecular functions. A molecular understanding of the local electrostatic environment, consistently for both specific (hydrogen-bonding) and nonspecific electrostatic (local polarity) interactions, is essential for a detailed understanding of these processes. Vibrational Stark Effect (VSE) has proven to be an extremely useful method to measure the local electric field using infrared spectroscopy of carbonyl and nitrile based probes. The nitrile chemical group would be an ideal choice because of its absorption in an infrared spectral window transparent to biomolecules, ease of site-specific incorporation into proteins, and common occurrence as a substituent in various drug molecules. However, the inability of VSE to describe the dependence of IR frequency on electric field for hydrogen-bonded nitriles to date has severely limited nitrile's utility to probe the noncovalent interactions. In this work, using infrared spectroscopy and atomistic molecular dynamics simulations, we have reported for the first time a linear correlation between nitrile frequencies and electric fields in a wide range of hydrogen-bonding environments that may bridge the existing gap between VSE and H-bonding interactions. We have demonstrated the robustness of this field-frequency correlation for both aromatic nitriles and sulfur-based nitriles in a wide range of molecules of varying size and compactness, including small molecules in complex solvation environments, an amino acid, disordered peptides, and structured proteins. This correlation, when coupled to VSE, can be used to quantify noncovalent interactions, specific or nonspecific, in a consistent manner.

Electrostatic interactions are key to C=O n-pi* shifts: an experimental proof - Haldar, Tapas; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2016)
Carbonyl n-pi* transitions are known to undergo blue shift in polar and hydrogen-bonding solvents. Using semiempirical expressions, previous studies hypothesized several factors like change in dipole moment and hydrogen-bond strength upon excitation to cause the blue shift. Theoretically, ground-state electrostatics has been predicted to be the key to the observed shifts, however, an experimental proof has been lacking. Our experimental results demonstrate a consistent linear correlation between IR (ground-state phenomenon) and n-pi* frequency shifts (involves both ground and excited electronic-states) of carbonyls in hydrogen-bonded and non-hydrogen-bonded environments. The carbonyl hydrogen-bonding status is experimentally verified from deviation in n-pi*/fluorescence correlation. The IR/n-pi* correlation validates the key role of electrostatic stabilization of the ground state toward n-pi* shifts and demonstrates the electrostatic nature of carbonyl hydrogen bonds. n-pi* shifts show linear sensitivity to calculated electrostatic fields on carbonyls. Our results portray the potential for n-pi* absorption to estimate local polarity in biomolecules and to probe chemical reactions involving carbonyl activation/stabilization.

Pick and choose the spectroscopic method to calibrate the local electric field inside proteins - Haldar, Tapas; Kashid, Somnath M.; Deb, Pranab; Kesh, Sandeep; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2016)
Electrostatic interactions in proteins play a crucial role in determining the structure function relation in biomolecules. In recent years, fluorescent probes have been extensively employed to interrogate the polarity in biological cavities through dielectric constants or semiempirical polarity scales. A choice of multiple spectroscopic methods, not limited by fluorophores, along with a molecular level description of electrostatics involving solute-solvent interactions, would allow more flexibility to pick and choose the experimental technique to determine the local electrostatics within protein interiors. In this work we report that ultraviolet/visible-absorption, infrared-absorption, or C-13 NMR can be used to calibrate the local electric field in both hydrogen bonded and non-hydrogen bonded protein environments. The local electric field at the binding site of a serum protein has been determined using the absorption wavelength as well as the carbonyl stretching frequency of its natural steroid substrate, testosterone. Excellent agreement is observed in the results obtained from two independent spectroscopic techniques.

Hydrocarbon chain-length dependence of solvation dynamics in alcohol-based deep eutectic solvents: a two-dimensional infrared spectroscopic investigation - Chatterjee, Srijan; Ghosh, Deborin; Haldar, Tapas; Deb, Pranab; Sakpal, Sushil S.; Deshmukh, Samadhan H.; Kashid, Somnath M.; Bagchi, Sayan (Journal of Physical Chemistry B, 2019)
Deep eutectic solvents (DESs) have gained popularity in recent years as an environmentally benign, inexpensive alternative to organic solvents for diverse applications in chemistry and biology. Among them, alcohol-based DESs serve as useful media in various applications due to their significantly low viscosity as compared to other DESs. Despite their importance as media, little is known how their solvation dynamics change as a function of the hydrocarbon chain length of the alcohol constituent. In order to obtain insights into the chain-length dependence of the solvation dynamics, we have performed two-dimensional infrared spectroscopy on three alcohol-based DESs by systematically varying the hydrocarbon chain length. The results reveal that the solvent dynamics slows down monotonically with an increase in the chain length. This increase in the dynamic timescales also shows a strong correlation with the concomitant increase in the viscosity of DESs. In addition, we have performed molecular dynamics simulations to compare with the experimental results, thereby testing the capacity of simulations to determine the amplitudes and timescales of the structural fluctuations on fast timescales under thermal equilibrium conditions.

Electrostatic manifestation of micro-heterogeneous solvation structures in deep-eutectic solvents: a spectroscopic approach - Chatterjee, Srijan; Haldar, Tapas; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry B, 2020)
Deep eutectic solvents have emerged as inexpensive green alternatives to conventional solvents for diverse applications in chemistry and biology. Despite their importance as useful media in various applications, little is known about the microscopic solvation structures of deep eutectic solvents around solutes. Herein, we show that the electrostatic field, which can be estimated both from infrared experiments and theory, can act as a unified concept to report on the microscopic heterogeneous solvation of deep eutectic solvents. Using a fluorophore containing the carbonyl moiety as the solute and the electrostatic field as a descriptor of the solvation structure of the deep eutectic solvents, we report the residue-specific distribution, orientation, and hydrogen bonding in deep eutectic solvents constituting of choline chloride and alcohols of varying chain-lengths. We observe that an increase in alcohol chain-length not only affects the alcohol's propensity to form hydrogen bond to the solute but also alters the spatial arrangement of choline cations around the solute, thereby leading to a microheterogeneity in the solvation structure. Moreover, to extend our electrostatic field based strategy to other deep eutectic solvents, we report an emission spectroscopy based method. We show that this method can be applied, in general, to all deep eutectic solvents, irrespective of their constituents. Overall, this work integrates experiments with molecular dynamics simulations to provide insights into the heterogeneous DES solvation.

Blue fluorescence of cyano-tryptophan predicts local electrostatics and hydrogen bonding in biomolecules - Haldar, Tapas; Chatterjee, Srijan; Alam, Md Nirshad; Maity, Pradip; Bagchi, Sayan (Journal of Physical Chemistry B, 2022)
Cyano-tryptophan is an unnatural fluorescent amino acid that emits in the visible region. Along with the structural similarity with tryptophan, the unique photophysical properties of this fluorophore make it an ideal probe for biophysical research. Herein, combining fluorescence spectroscopy, infrared spectroscopy, and molecular dynamics simulations, we show that the cyano-tryptophan's emission energy quantifies the underlying bond-specific noncovalent interactions in terms of the electric field. We further report the use of fluorophore's emission energy to predict its hydrogen bond characteristics. We demonstrate that combining experiments with molecular dynamics simulations can provide the hydrogen bonding status of the nitrile moiety. In addition, we report a method to differentiate between aqueous and nonaqueous hydrogen-bonding partners. Using a phenomenological approach, we demonstrate that the presence of the cyano-indole moiety is responsible for the distinct correlations between the fluorophore's emission and the electrostatic forces on the nitrile bond. As indole is a privileged scaffold for both native amino acids and nucleobases, cyano-indoles will have many multifaceted applications.